Constancy of colour perception: Empirical investigation and mathematical model - VILIŪNAS, V.; VAITKEVIČIUS, H.; KULIKOWSKI, J.; ZANAIB, A. (Psichologija, 1997)
The method to estimate the color constancy is suggested. The experimental results confirm the hypothesis of color constancy linear model. The linear operator calculated from the chromaticity coordinates of three chips under two different illuminations. The analysis of this linear operator is performed to clear up the physiological mechanism.